Similarity hypothesis: understanding of others with autism spectrum disorders by individuals with autism spectrum disorders - Komeda, Hidetsugu (Frontiers in Human Neuroscience, 2015)
Individuals with an autism spectrum disorder (ASD) are generally thought to lack empathy. However, according to recent empirical and self-advocacy studies, individuals with ASD identify with others with ASD. Based on mutual understanding, individuals with ASD respond empathically to others with these disorders. Results have shown that typically developing (TD) adults identify with typically developing fictional characters, and that such identification plays a critical role in social cognition. TD individuals retrieve episodes involving TD individuals faster than they retrieve episodes involving ASD individuals. Individuals with ASD also show a “similarity effect” whereby they retrieve stories involving ASD individuals more effectively when the stories have consistent outcomes than when they have inconsistent outcomes. In this context, I hypothesized that similarities between a perceiver and a target facilitate cognitive processing. This hypothesis was named the “similarity hypothesis”. Perceivers empathize with targets similar to themselves, which facilitates subsequent cognitive processing. Behavioral and neuroimaging studies are reviewed based on the similarity hypothesis.